Studies on the effects of N-ethylmaleimide (NEM) in the urinary bladder of Bufo marinus - Marples, D (1990)
This thesis sets out a characterisation of the effects of the sulphydryl agent N-ethylmaleimide (NEM) on water flow across the urinary bladder of the toad, Bufo marinus. and compares the effects of NEM with those of vasopressin (VP). This has been done using functional, biochemical, and ultrastructural studies of bladders treated with NEM or VP. The introduction reviews the action of VP in the toad bladder, and summarises the previous experiments with NEM in this tissue. The results show that NEM causes a specific, irreversible, increase in transepithelial osmotic water flow, but inhibits sodium transport. The increase in water flow does not appear to be mediated by cAMP, or changes of pH or calcium ion concentration, but can be inhibited by low pH, raised calcium, or disruption of the cytoskeleton or cellular metabolism. NEM-induced water flow is additive with that induced by a sub-maximal, but not a maximal, VP dose. NEM treatment leaves the overall epithelial structure intact, while causing changes consistent with increased water flow through the granular cells. Membrane fusion profiles, similar to those seen after VP stimulation, are visible at the apical plasma membrane, and particle aggregates morphologically identical to those believed to mediate the hydrosmotic response to VP can be visualised by freeze-fracture electron microscopy. These results suggest that NEM induces a specific increase in transepithelial water flow by activating, via one or more sulphydryl reactions, the cellular apparatus stimulated by VP. This activation must occur distal to cAMP production, but proximal to cytoskeletal involvement. NEM may prove valuable in understanding the action of vasopressin, by providing an agonist that acts later in the pathway than others currently available. The implications of the experiments reported here, and suggestions for further work, are discussed.